Gender norms among "Landless" youth: evidence for the social practice of nursing - Luiz Fabiano Zanatta; Maria Tereza Ruiz-Cantero; Elisa Chilet-Rossel; Carlos Álvarez-Dardet; José Roberto da Silva Brêtas (SciELO, 2018)
ABSTRACT Objective Analyzing the relationship between socio-demographic characteristics of youth from the Landless Rural Workers' Movement in Brazil (MST) regarding the prevalence ratio being in accordance with gender norms. Method A cross-sectional study conducted during a Journey of Agroecology carried out in the State of Paraná with young people (15 to 29 years) of both genders. Data collection was conducted through questionnaires. Data analysis compared variables regarding gender norms with sociodemographic variables, and a Prevalence Ratio (PR) was calculated with a confidence interval (CI) set at 95% in order to determine this relationship. Results The study sample was comprised of 147 young people. A higher prevalence was found in accordance with gender norms (PR with CI at 95%) among women compared to men, and that sociodemographic characteristics (lower education level, those living in occupation camps, who do not have white skin and with religious belief) were social indicators for such positioning among both genders. Conclusion The byproduct of a patriarchal gender system has led more young girls to internalization and a reaffirmation of gender norms, highlighting an important field for social nursing practices in order to contribute to the transformation of this reality.